Potential of Hydrogen Production from Pepper Waste Gasification - Güngör, Afşin; Akyürek, Zuhal; Akyüz, Ali Özhan (Tayfun UYGUNOĞLU, 2019)
Gasification is a promising clean energy technology for hydrogen production and sustainable waste management. Biomass residues have great potential to produce renewable hydrogen. In this study, the potential of production of hydrogen from pepper residues was determined via a modeling study of air/steam gasification system. The input carbon of the feedstock was assumed to be fully gasified in the numerical model calculations performed for the downdraft gasifier system. Air to fuel ratio (A/F) and steam to fuel (S/F) ratio are taken as 0.05 because of the high oxygen content in pepper waste. The temperature of the gasifier is 877 °C for the developed mathematical model. The modeling study results revealed high hydrogen content in the producer gas derived from pepper waste gasification which has obtained as 49.08 %.

Gazlaştırma, hidrojen üretimi ve sürdürülebilir atık yönetimi için umut verici bir enerji teknolojisidir. Biyokütle atıkları yenilenebilir hidrojen üretme konusunda büyük potansiyele sahiptir. Bu çalışmada, biber atıklarının hidrojen üretim potansiyelini hava-buhar gazlaştırma teknolojisi ile incelemek için bir modelleme çalışması yapılmıştır. Aşağı çekiş gazlaştırma sistemi için geliştirilen sayısal model, yakıt karışımındaki tüm karbonun gazlaştırıldığını varsayar. Biber artığındaki yüksek O2 içeriğinden dolayı hava/yakıt ve buhar/yakıt oranı 0,05 olarak alınmıştır. Geliştirilen model için gazlaştırma sıcaklığı 877 °C 'dir. Modelleme sonucuna göre, biber atıklarının gazlaştırılması ile üretilen gazdaki hidrojen içeriği % 49,08 olarak elde edilmiştir.
Biber Atıklarının Gazlaştırılmasının Hidrojen Üretim Potansiyeli
Keywords: Engineering; Mühendislik